Integration of Guidance and Counseling in Principal Leadership: Jawdat Ezzat Atwi's Perspective - Siti Maghfiroh; Achmad Muhlis (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
This study aims to analyze the concept of improving the quality of education through the integration of guidance and counseling (GC) services under the leadership of the school principal, referring to the thoughts of Jawdat Ezzat Atwi in Al-Idarah al-Madrasiyyah al-Hadithah. The focus of the study is directed at examining how the principal, as an educational leader, is able to optimize the function of GC as a strategic instrument in developing students’ potential, enhancing discipline, shaping character, and addressing learning-related problems. This research employs a qualitative approach through literature analysis and interpretation of Atwi’s ideas on modern school management, particularly in relation to supervision, program coordination, and the development of a conducive learning environment. The findings indicate that effective integration of GC requires principal leadership that is visionary, participatory, and oriented toward quality improvement. Atwi’s perspective underscores the importance of systematic, collaborative, and student-centered school governance, enabling GC services to function optimally as an integral component of educational quality enhancement. Thus, the integration of GC under principal leadership, as conceptualized by Atwi, constitutes a strategic approach to realizing quality, humanistic, and developmentally responsive education in the contemporary era.